राजकीय-महापुरुषाः भागः-2 - (:unkn) unknown (Kavikulguru Kalidas Sanskrit Vishwavidyalaya Ramtek Nagpur Maharashtra, 2004)
This is a Bal sahitay in Sanskrit. The biography of Pandit Jawaharlal Nehru, Dr. Rajendra Prasad, Lalbahadur Shastri and Dr. Hedgewar is given in this book.
Rajkiya-Mahapurushah Bhagah-2
Keywords: Children's literature; Sanskrit